Soil carbonate drives local adaptation in Arabidopsis thaliana. (18th June 2019) - Terés, Joana; Busoms, Silvia; Perez Martín, Laura; Luís‐Villarroya, Adrián; Flis, Paulina; Álvarez‐Fernández, Ana; Tolrà, Roser; Salt, David E.; Poschenrieder, Charlotte
Abstract: High soil carbonate limits crop performance especially in semiarid or arid climates. To understand how plants adapt to such soils, we explored natural variation in tolerance to soil carbonate in small local populations (demes) of Arabidopsis thaliana growing on soils differing in carbonate content. Reciprocal field‐based transplants on soils with elevated carbonate (+C) and without carbonate (−C) over several years revealed that demes native to (+C) soils showed higher fitness than those native to (−C) soils when both were grown together on carbonate‐rich soil. This supports the role of soil carbonate as a driving factor for local adaptation. Analyses of contrasting demes revealed key mechanisms associated with these fitness differences. Under controlled conditions, plants from the tolerant deme A1(+C) native to (+C) soil were more resistant to both elevated carbonate and iron deficiency than plants from the sensitive T6(−C) deme native to (−C) soil. Resistance of A1(+C) to elevated carbonate was associated with higher root extrusion of both protons and coumarin‐type phenolics. Tolerant A1(+C) also had better Ca‐exclusion than sensitive T6(−C) . We conclude that Arabidopsis demes are locally adapted in their native habitat to soils with moderately elevated carbonate. This adaptation is associated with both enhanced iron acquisition and calcium exclusion. Abstract : Soil carbonate is revealed as a driving factor for local adaptation in Arabidopsis thaliana . Carbonate tolerance is characterized by higher root exudation of H + and coumarins but not by higher ferric reductase activity.